2016
DOI: 10.5430/ijhe.v5n1p208
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Planned Behavior Predicts Graduation Intentions of Canadian and Israeli Postsecondary Students with and without Learning Disabilities/Attention Deficit Hyperactivity Disorder

Abstract: We tested the ability of Ajzen's Theory of Planned Behavior (TPB) model to predict intention to graduate among Canadian and Israeli students with and without a learning disability / attention deficit hyperactivity disorder (LD/ADHD). Results based on 1486 postsecondary students show that the model's predictors (i.e., attitude, subjective norms, perceived behavioral control related to graduation) predicted between 32% and 59% of the variability in intention to graduate. Gender made a minor contribution to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
2
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 29 publications
(32 reference statements)
1
14
2
5
Order By: Relevance
“…The Theory of Planned Behavior has been used to predict academic persistence and graduation of students with disabilities in general (Fichten et al, 2014b(Fichten et al, , 2016. In the present investigation it is used to predict intention to graduate among students with LD and those with mental health related disabilities.…”
Section: Theory Of Planned Behaviormentioning
confidence: 91%
See 1 more Smart Citation
“…The Theory of Planned Behavior has been used to predict academic persistence and graduation of students with disabilities in general (Fichten et al, 2014b(Fichten et al, , 2016. In the present investigation it is used to predict intention to graduate among students with LD and those with mental health related disabilities.…”
Section: Theory Of Planned Behaviormentioning
confidence: 91%
“…This measure is available in Fichten et al (2016). All subscales, except Attitude toward graduation, use a 6-point Likert scale (1=Strongly disagree to 6= Strongly agree).…”
Section: School Related Questionsmentioning
confidence: 99%
“…n a recent research study, it was found that 30-50 out of every 100 graduate students currently enrolled in graduate programming drop out before graduation (Fichton et al 2016). In North America, over ten percent of graduate students have a variety of disabilities such as learning disabilities (LD), Attention Deficit Hyperactivity Disorder, (ADHD), mental health disorders, and other physical impairments that can often impair a student's ability to graduate from postsecondary graduate programs, and can pose unique barriers, particularly when writing their final thesis/dissertation (Fichton et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The Theory of Planned Behavior is employed in various studies in different fields of study. In fact, in the field of education, the TPB model has successfully predicted drop-out and graduation behavior (Fichten et al 2016), and the adoption of Public Relations faculty of online courses features (Knabe 2012). The potential of TPB model in analyzing fertility intentions as an aid to public policy is also explored (Ajzen and Klobas 2013).…”
Section: Introductionmentioning
confidence: 99%